2022
DOI: 10.1186/s12879-022-07539-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal distribution of tuberculosis and the effects of environmental factors in China

Abstract: Background Although the World Health Organization reports that the incidence of tuberculosis in China is decreasing every year, the burden of tuberculosis in China is still very heavy. Understanding the spatial and temporal distribution pattern of tuberculosis in China and its influencing environmental factors will provide effective reference for the prevention and treatment of tuberculosis. Methods Data of TB incidence from 2010 to 2017 were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Although only limited evidence is currently available regarding the association between meteorological factors and TB incidence at the nationwide in China, the findings of the present study are basically consistent with existing reports that Atemp, ARH, AWS, PRE and SD were associated with TB incidence [ 4 , 10 , 11 , 14 , 33 , 34 ]. A study conducted in 16 cities in Anhui province reported that low temperature increased the risk of TB hospitalizations [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although only limited evidence is currently available regarding the association between meteorological factors and TB incidence at the nationwide in China, the findings of the present study are basically consistent with existing reports that Atemp, ARH, AWS, PRE and SD were associated with TB incidence [ 4 , 10 , 11 , 14 , 33 , 34 ]. A study conducted in 16 cities in Anhui province reported that low temperature increased the risk of TB hospitalizations [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…China, the third-largest contributor to global TB burden [ 1 ], reported an incidence rate of 45.37/100,000 in 2021 [ 3 ]. While China has made commendable progress in TB control, ongoing attention is required for high-risk areas and populations [ 4 ]. Therefore, a comprehensive understanding of the demographic, temporal, and spatial distribution of TB is essential for effective interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Every year, in uenza virus subtypes alternate in circulation, and this may be in uenced by factors such as population immunity levels and environmental conditions [20,21]. Dominant in uenza virus subtypes continually shift, showing a certain pattern of alternation.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, I < 0 indicates negative spatial correlation, with a smaller value indicating a greater spatial difference. When I = 0, it indicates spatial randomness [9]. While the latter is employed to assess the impact of individual locations on the magnitude of the global statistic and to identify the location and types of clusters.…”
Section: Spatial Autocorrelation Methodsmentioning
confidence: 99%